2007
DOI: 10.3748/wjg.v13.i3.378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of emodin on pancreatic fibrosis in rats

Abstract: AIM:To establish the rats model of chronic fibrosing pancreatitis and to prove the anti-fibrotic effect of emodin in chronic pancreatitis with fibrosis. METHODS:Fifty rats were randomly divided into five groups, 10 rats in each group. Trinitrobenzene sulfonic acid (TNBS) was infused into the pancreatic duct to induce chronic pancreatitis in rats (except for normal group). Emodin-treated rats were fed with different doses of emodin (20, 40 and 80 mg/kg body weight) for 28 d, while normal group and control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
1
23
0
1
Order By: Relevance
“…As a result of this screening, emodin (1,3,8-trihydroxy-6-methylanthraquinone), a natural active compound in the herb Rheum palmatum L. was shown to stimulate the AMPK pathway. Some previous studies have suggested that emodin has an beneficial effect on energy metabolism, including adipocyte differentiation (14), anti-fibrotic effect on pancreatic fibrosis (15), and liver (16). However, validation of the molecular mechanism and the anti-diabetic effects of this compound has not been fully examined.…”
Section: Ampkmentioning
confidence: 99%
“…As a result of this screening, emodin (1,3,8-trihydroxy-6-methylanthraquinone), a natural active compound in the herb Rheum palmatum L. was shown to stimulate the AMPK pathway. Some previous studies have suggested that emodin has an beneficial effect on energy metabolism, including adipocyte differentiation (14), anti-fibrotic effect on pancreatic fibrosis (15), and liver (16). However, validation of the molecular mechanism and the anti-diabetic effects of this compound has not been fully examined.…”
Section: Ampkmentioning
confidence: 99%
“…26 Emodins has anti angiogenetic effect 27 Plenty of pharmaceutical studies indicates that emodins have anti inflammatory, anticancer and antimicrobial activity anti-cancer, anti-microbial and antiinflammatory effects. 28 The UV-Visible spectra were performed to identify the compounds containing σ-bonds, π-bonds, and lone pair of electrons, chromophores and aromatic rings The profile showed the peaks at 208.04, 271.94 and 881.96 nm with the absorption 2.76,0.72 and 0.04 respectively Table 3 and Figure 1. The result confirms the occurrence of peaks at 208-881 nm reveals that the absorption bands are due to the presence of flavonoids, phenol and its derivatives in the bryonopsis laciniosa fruit.…”
Section: Figure 1: Uv-vis Spectral Analysis Of Bryonopsis Laciniosa Fmentioning
confidence: 99%
“…It has been demonstrated to inhibit the fibrosis process of various organs, including the liver, pancreas, peritoneum and kidney (1)(2)(3). Emodin suppresses p38 phosphorylation to inhibit cell proliferation and fibronectin expression in mesangial cells cultured in high-glucose solution (4).…”
Section: Introductionmentioning
confidence: 99%